The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jbm4.10495
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Hypophosphatasia in Adults Presenting With Metatarsal Stress Fracture: Proof‐of‐Concept for a Case‐Finding Strategy

Abstract: Hypophosphatasia (HPP) is caused by loss‐of‐function mutations in ALPL resulting in decreased alkaline phosphatase (ALP) activity. Metatarsal stress fracture (MSF) is a common clinical feature of hypophosphatasia in adults. In this study, the primary objectives were to determine whether new cases of ALPL variants could be identified in patients with MSF and who also had serum ALP concentration below the reference range and to phenotype their clinical course. Electronic health records were queried for adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 23 Since metatarsal fractures are suggestive of HPP, Koehler et al focused on this population and found 0.12% prevalence of pathogenic ALPL variants in a population of 1611 metatarsal fractures, a proportion that rose to 15% when low ALP measurement was associated. 24 In our study, the same approach using clinical, biological and imaging features identified 69 patients with at least three evocative symptoms of HPP in addition to persistently low ALP values (possible HPP) among which 11 were found to have genetically proven HPP, representing a diagnosis rate of at least 15.9%. This value is probably underestimated since only 18 patients benefited from genetic testing, corresponding to a diagnosis rate of 61.1% of the tested patients.…”
Section: Discussionmentioning
confidence: 68%
“… 23 Since metatarsal fractures are suggestive of HPP, Koehler et al focused on this population and found 0.12% prevalence of pathogenic ALPL variants in a population of 1611 metatarsal fractures, a proportion that rose to 15% when low ALP measurement was associated. 24 In our study, the same approach using clinical, biological and imaging features identified 69 patients with at least three evocative symptoms of HPP in addition to persistently low ALP values (possible HPP) among which 11 were found to have genetically proven HPP, representing a diagnosis rate of at least 15.9%. This value is probably underestimated since only 18 patients benefited from genetic testing, corresponding to a diagnosis rate of 61.1% of the tested patients.…”
Section: Discussionmentioning
confidence: 68%